The Role of Entrepreneurship Orientation and Market Orientation on Product Innovation and Business Performance at SMEs Restaurants in Lamongan - Mohammad Yaskun; Sudarmiatin (Enrichment : Journal of Management, 2021)
This study analyzes business performance in the context of product innovation which is influenced by entrepreneurial orientation and market orientation. Based on the results of the path analysis, it shows that product innovation is an intervening variable on the variable of competitive advantage. The results also show that entrepreneurial orientation does not have a significant effect on product innovation while market orientation has a significant effect. Entrepreneurial orientation and product innovation have a significant effect on business performance, while market orientation has no significant effect.